POTENTIAL OF BIOGAS AND BIOMETHANE FROM ORGANIC ANIMAL WASTE - Iesipov, O. V.; Hryn, Ye. L. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2023)
The problem of efficient waste recycling and disposal is one of the most acute in the world. In recent years, considerable attention has been paid to the issues of rational management of agricultural waste in Ukraine by both the authorities and the scientific community. The solution to the problem is possible by implementing effective measures for fast, safe recycling of waste and obtaining a positive economic and environmental effect from the disposal and reuse of raw materials. Due to the huge territorial potential and a large number of agricultural lands, relatively low population density and relatively favorable climate, the country has good initial conditions for the production of trade and use of bioenergy. Biomethane can be used as a fuel for cars. And after the production of biogas from biomass, it becomes a biofertilizer that is environmentally friendly and its composition is not inferior to chemical fertilizers. Another factor in favor of biogas is that biogas plants (BGP) do not depend on the weather (sunny days, gusts of wind) and can ensure the smooth operation of power plants with a stable supply of raw materials. In establishing the theoretically possible biogas and biomethane potential, only those animals are considered that have the largest share in the total livestock production of the country and can make a significant contribution to biogas production. After purification of biogas from impurities, the obtained biomethane through the gas distribution network is fed to power plants for further energy production or used as fuel for cars. It should be noted that one of the advantages of biogas plants is the production of organic fertilizers in the process of anaerobic digestion of biomass in a biogas plant. Their use will not only improve the physical and mechanical properties of the soil, increase the yield of agricultural crops, but in the future will help to produce competitive environmentally friendly products both on the domestic and foreign markets.